Preclinical antitumor activity of the diindolylmethane formulation in xenograft mouse model of prostate cancer - Kiselev, V.I.; Drukh, V.M.; Muyzhnek, E.L.; Kuznetsov, I.N.; Pchelintseva, O.I.; Paltsev, M.A. (Experimental Oncology, 2014)
Aim: Preclinical study of the specific anticancer pharmacological activity of the formulation containing active substance 3,3ʹ-diindolylmethane (DIM), cod liver oil, polysorbate 80 and α-tocopherol acetate (vitamin E), in vivo in a xenograft animal model of LNCaP. Materials and Methods: The DIM, cod liver oil, polysorbate 80 and α-tocopherol acetate (vitamin E) formulation was intragastrically administered to BALB/c-nude (nu/nu) mice during 33 days post inoculation at the dose of 133 mg/kg/day. Antitumor activity of the test drug was estimated by the rate of tumor growth inhibition (T/C% — treated versus control), dividing the tumor volumes from treatment groups with the control groups. Results: Statistically significant tumor xenograft regressions have been shown in group which received the DIM, cod liver oil, polysorbate 80 and α-tocopherol acetate (vitamin E) on the 37th day of observation post inoculation. The highest antitumor activity was achieved on the 39th day (T/C = 16,8%). Therapeutic effect lasts for 6 days after the end of therapy period. Conclusion: Our findings demonstrate inhibitory effect of the formulation on tumor development in the xenograft animal model due to the tumor growth rate reduction. Key Words: 3,3´-diindolylmethane, bioavailability, anticancer activity, xenograft model, LNCaP cell line, preclinical studies.